Apreciação da qualidade individual ou do serviço utilizando os GDHS na versão 2000. - Edgar Ferreira; Carlos Reis; Rosa Maria Batista (Acta Médica Portuguesa, 2002)
The Diagnosis Related Groups (DRG) aren't only a management instrument useful for managers and technicians but also to physicians as professionals who are in fact their producers. The DRG may be used as guides of good clinical practice and as quality pointer. Never as an absolute truth or way of judging something. We study the new arriving 2000 DGR version and how to use it as a guide and quality indicator for physicians who wants to improve his quality, skills and proficiency in clinical practice. We give a brief look on the DGR world expansion and the bibliography to deep the knowledge in this subject.